Whole Brain Radiation Therapy Plus Stereotactic Radiosurgery in the Treatment of Brain Metastases Leading to Improved Survival in Patients With Favorable Prognostic Factors - Khan, Muhammad; Lin, Jie; Liao, Guixiang; Tian, Yunhong; Liang, Yingying; Li, Rong; Liu, Mengzhong; Yuan, Yawei (Frontiers in Oncology, 2019)
Background: Significantly better local control is achieved with combination of whole brain radiotherapy and stereotactic radiosurgery in the treatment of multiple brain metastases. However, no survival benefit was reported from this advantage in local control. Objective: The objective of this study was to review the available evidence whether better local control achieved with whole brain radiotherapy plus stereotactic radiosurgery leads to any benefit in survival in patients with favorable prognostic factors. Methods and Materials: Electronic databases (PubMed, MEDLINE, and Cochrane Library) were searched until Oct 2018 to identify studies published in English that compared efficacy of whole brain radiotherapy plus stereotactic radiosurgery vs. whole brain radiotherapy alone or stereotactic radiosurgery alone in patients with brain metastases stratified on prognostic indices (Recursive Partitioning Analysis and Diagnosis-Specific Graded Prognostic Assessment). Primary outcome was survival. Results: Five studies (n = 2728) were identified, 3 secondary analyses of the previously published RCTs and 2 retrospective studies, meeting the inclusion criteria. whole brain radiotherapy plus stereotactic radiosurgery showed improved survival in brain metastatic cancer patients with better prognostic factors particularly when compared to whole brain radiotherapy only. Its survival advantage over stereotactic radiosurgery only was limited to non-small cell lung cancer primary tumor histology. Conclusions: Whole brain radiotherapy in combination with stereotactic radiosurgery may improve survival and could be recommended selectively in patients with favorable prognostic factors particularly in comparison to whole brain radiotherapy only.